The determination of the conduction mechanism and optical band gap of fluorescein sodium salt - Yakuphanoğlu, Fahrettin; Sekerci, Memet; Evin, Ertan (Elsevier Science Bv, 2006)
The electrical conductivity and optical properties of fluorescein sodium salt in the temperature range of 295-370K have been investigated. Various conduction models described in the literature were used to elucidate the charge transport mechanism of the compound. It is found that the charge transfer mechanism of the compound is understood in terms of grain boundary scattering. It can be evaluated that the obtained electronic parameters such as mobility, conductivity at room temperature, activation energy and optical band gap suggest that the compound is an organic semiconductor. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: organic semiconductor; conductivity; optical band gap